KONSTRUKSI IDEOLOGI MUHAMMADIYAH DALAM TAFSIR AL-AZHAR: SEBUAH ANALISIS WACANA KRITIS - Salsadilah, Nijma Auliah; Indal Abror (IAIN KENDARI, 2025)
This research analyzes how Muhammadiyah ideology influences Buya Hamka's interpretation in his Tafsir Al-Azhar through Fairclough's Critical Discourse Analysis (CDA). Using library research methodology with a qualitative approach, this study examines three selected Quranic verses: QS. Ali 'Imran :104 (structured da'wah), QS. Al-Baqarah :170 (rationalism and anti-taqlid), and QS. Al-Ma'un :1-7 (concrete social action). The findings reveal that Hamka consistently employs lexical choices and discourse strategies that reflect three dimensions of Muhammadiyah ideology: (1) structured organization, (2) rationalism, and (3) concrete social action. At the textual level, word choices such as